Integration analyses of structural variations and differential gene expression associated with beef fatty acid profile in Nellore cattle - Berton, Mariana Piatto [UNESP]; de Lemos, Marcos Vinícius Antunes [UNESP]; Stafuzza, Nedenia Bonvino; Simielli Fonseca, Larissa Fernanda [UNESP]; Silva, Danielly Beraldo dos Santos [UNESP]; Peripolli, Elisa [UNESP]; Pereira, Angélica S. C.; Magalhães, Ana Fabricia Braga [UNESP]; Albuquerque, Lucia G. [UNESP]; Baldi, Fernando [UNESP] (Wiley, 2022)
This study aimed to integrate analyses of structural variations and differentially expressed genes (DEGs) associated with the beef fatty acid (FA) profile in Nellore cattle. Copy numbers variation (CNV) detection was performed using the penncnv algorithm and CNVRuler software in 3794 genotyped animals through the High-Density Bovine BeadChip. In order to perform the genomic wide association study (GWAS), a total of 963 genotyped animals were selected to obtain the intramuscular lipid concentration and quantify the beef FA profile. A total of 48 animals belonging to the same farm and management lot were extracted from the 963 genotyped and phenotyped animals to carry out the transcriptomic and differentially expressed gene analyses. The GWAS with extreme groups of FA profiles was performed using a logistic model. A total of 43, 42, 66 and 35 significant CNV regions (p < 0.05) for saturated, monounsaturated, polyunsaturated and omega 3 and 6 fatty acids were identified respectively. The paired-end sequencing of 48 samples was performed using the Illumina HiSeq2500 platform. Real-time quantitative PCR was used to validate the DEGs identified by RNA-seq analysis. The results showed several DEGs associated with the FA profile of Longissimus thoracis, such as BSCL2 and SAMD8. Enriched terms as the cellular response to corticosteroid (GO:0071384) and glucocorticoid stimulus (GO:0071385) could be highlighted. The identification of structural variations harboring candidate genes for beef FA must contribute to the elucidation of the genetic basis that determines the beef FA composition of intramuscular fat in Nellore cattle. Our results will contribute to the identification of potential biomarkers for complex phenotypes, such as the FA profile, to improve the reliability of the genomic predictions including pre-selected variants using differentiated weighting in the genomic models.
Keywords: Bos indicus; copy numbers variation; genomic selection; genomic wide association study; RNA-seq